Effects of soybean meal versus processed whole soybean diets on the performance of young bulls and the fatty acid composition of intramuscular fat - Oliveira, C. V. R.; Schoonmaker, J. P.; Casagrande, D. R.; Machado Neto, O. R. [UNESP]; Reis, V. A. A.; Teixeira, P. D.; Santos, L. R.; Ladeira, M. M. (Csiro Publishing, 2020)
Context It is hypothesised that the use of processed soybean for feedlot beef cattle improves feed efficiency and produces beef with a better fatty acid profile for human health. Aims This study aimed to evaluate average daily gain, feed efficiency, carcass traits, chemical composition, fatty acid profile and colour in the beef of young bulls fed diets with ground or extruded soybean. Methods A total of 60 young Zebu bulls (Nellore or Nellore crossed with other Zebu breeds) with an average initial liveweight of 320 +/- 8.12 kg and an average initial age of 20 +/- 2 months were randomly assigned to receive one of the following diets for 84 days: dehulled and defatted soybean meal (3.22% of ether extract), ground soybean (6.51% of ether extract) or extruded soybean (6.37% of ether extract). The fatty acid profiles of these animals were analysed using high-resolution gas chromatography. The CIE L*a*b* colour space model was used to numerically describe the colour during the aging period (0, 7, 14 and 21 days). Key results Diet had no effect on the average daily gain, feed efficiency or carcass traits of the animals (P> 0.05). Protein, ether extract and ash composition of theLongissimus lumborum(LL) muscle were not affected (P> 0.30) by the use of processed soybean grains. The ground soybean diet decreased oleic acid and C18:2 c9, t11 concentrations, but increased C18:2 t10, c12 and trans-octadecenoic acid isomer concentrations in the LL muscle compared with those in the dehulled and defatted soybean meal and extruded soybean diets (P< 0.05). Muscle from bulls fed processed soybean exhibited greater concentrations of stearic acid and saturated fatty acids, and a lower concentration of unsaturated fatty acids, as well as a decreased unsaturated fatty acids : saturated fatty acids ratio (P< 0.05). Processed soybean grains did not affect (P> 0.05) the LL muscle pH or colour. Conclusions The use of ground or extruded soybean did not affect the performance, carcass traits, LL protein, ether extract or ash composition, and had no impact on beef colour compared with the diet containing soybean meal. Processed whole soybeans in the diet did not increase unsaturated fatty acids or conjugated linoleic acid in beef compared with a diet without soybean meal. Implications Up to 20% of ground or extruded soybean in feedlot beef cattle can be used as a replacement for soybean meal and corn.
Keywords: conjugated linoleic acid; extruded soybean; grain processing; lipids; oilseeds